Stroke and physiological relationships during the incremental front crawl test: outcomes for planning and pacing aerobic training - Almeida, Tiago A. F.; Espada, Mário C.; Massini, Danilo A.; Macedo, Anderson G.; Castro, Eliane A.; Ferreira, Cátia C.; Reis, Joana F.; Pessôa Filho, Dalton M. (Frontiers in Physiology, 2023)
Purpose: This study aimed to evaluate the physiological responses associated with the stroke length (SL) and stroke rate (SR) changes as swimming velocity increases during an incremental step-test. Moreover, this study also aimed to verify if SL and SR relationships toward maximal oxygen uptake (V̇O2max), gas respiratory compensation point (RCP), exchange threshold (GET), and swimming cost can be applied to the management of endurance training and control aerobic pace. Methods: A total of 19 swimmers performed the incremental test until volitional exhaustion, with each stage being designed by percentages of the 400 m (%v400) maximal front crawl velocity. V̇O2max, GET, RCP, and the respective swimming velocities (v) were examined. Also, the stroke parameters, SL, SR, the corresponding slopes (SLslope and SRslope), and the crossing point (Cp) between them were determined. Results: GET and RCP corresponded to 70.6% and 82.4% of V̇O2max (4185.3 ± 686.1 mL min-1), and V̇O2 at Cp, SLslope, and SRslope were observed at 129.7%, 75.3%, and 61.7% of V̇O2max, respectively. The swimming cost from the expected V̇O2 at vSLslope (0.85 ± 0.18 kJ m-1), vSRslope (0.77 ± 0.17 kJ m-1), and vCp (1.09 ± 0.19 kJ m-1) showed correlations with GET (r = 0.73, 0.57, and 0.59, respectively), but only the cost at vSLslope and vCp correlated to RCP (0.62 and 0.69) and V̇O2max (0.70 and 0.79). Conclusion: SL and SR exhibited a distinctive pattern for the V̇O2 response as swimming velocity increased. Furthermore, the influence of SL on GET, RCP, and V̇O2max suggests that SLslope serves as the metabolic reference of heavy exercise intensity, beyond which the stroke profile defines an exercise zone with high cost, which is recommended for an anaerobic threshold and aerobic power training. In turn, the observed difference between V̇O2 at SRslope and GET suggests that the range of velocities between SL and SR slopes ensures an economical pace, which might be recommended to develop long-term endurance. The results also highlighted that the swimming intensity paced at Cp would impose a high anaerobic demand, as it is located above the maximal aerobic velocity. Therefore, SLslope and SRslope are suitable indexes of submaximal to maximal aerobic paces, while Cp’s meaning still requires further evidence.